Demographic pressure in Serra do Mar State Park and its buffer zone, southeastern Brazil - Starzynski, Roberto; Simões, Silvio Jorge Coelho [UNESP]; Soares, Paulo Valladares [UNESP]; Mendes, Tatiana Sussel Gonçalves [UNESP] (Springer Nature, 2018)
The Serra do Mar State Park forms a green corridor that connects significant remnants of the Atlantic Forest in Brazil, a region that presents great biodiversity. However, the mounting pressure exerted on it by disorderly urban expansion around conservation unit areas is a cause for concern. Thereby, this paper aims to analyze a geographical and demographic characterization of Serra do Mar State Park and its buffer zone in order to identify regions under the greatest pressure and provide subsidies for developing public policies. The study is based on a cartographic representation using a geographic information system associated with the 2010 Census demographic data, which has been conducted by the Brazilian Institute of Geography and Statistics (IBGE in Portuguese acronym). The study area covers the territory of 32 municipalities and it was found that almost 25,000 inhabitants live inside the park while approximately 712,000 residents live inside its buffer zone.
Keywords: Buffer zone; Conservation unit; Demographic pressure; Geospatial analysis